Feasibility Tests on Concrete with Very-High-Volume Supplementary Cementitious Materials - Keun-Hyeok Yang; Yong-Su Jeon (The Scientific World Journal)
The objective of this study is to examine the compressive strength and durability of very high-volume SCM concrete. The prepared 36 concrete specimens were classified into two groups according to their designed 28-day compressive strength. For the high-volume SCM, the FA level was fixed at a weight ratio of 0.4 and the GGBS level varied between the weight ratio of 0.3 and 0.5, which resulted in 70–90% replacement of OPC. To enhance the compressive strength of very high-volume SCM concrete at an early age, the unit water content was controlled to be less than 150 kg/m3, and a specially modified polycarboxylate-based water-reducing agent was added. Test results showed that as SCM ratio (RSCM) increased, the strength gain ratio at an early age relative to the 28-day strength tended to decrease, whereas that at a long-term age increased up to RSCM of 0.8, beyond which it decreased. In addition, the beneficial effect of SCMs on the freezing-and-thawing and chloride resistances of the concrete decreased at RSCM of 0.9. Hence, it is recommended that RSCM needs to be restricted to less than 0.8–0.85 in order to obtain a consistent positive influence on the compressive strength and durability of SCM concrete.